Mapping of Health Conditions Associated With E-Waste Activities at Agbogbloshie, Accra - Adusei, A. A. (University of Ghana, 2015)
E-waste, known also as electronic or electrical waste, is a term used to describe discarded electronic devices which use either electricity or battery for operation. These include, computers, televisions, mobile phones, printers and many more. Background: E-waste activities include the collection of discarded e-waste materials from various locations. These are then brought to the e-waste site for sorting, dismantling and open burning to extract the precious elements. The activities of the e-waste workers expose them to health hazards such as injuries and skin conditions. Objectives: The objective of this study was to conduct a spatial assessment and analysis of health conditions associated with different e-waste activities at different activity spaces at Agbogbloshie. Methods: A total of one hundred and twelve (112) subjects were conveniently sampled from the activity spaces. The various health outcomes of interest were assessed using direct physical examination and the administration of open and close ended questionnaires. Results: A map showing the various activity spaces at the Agbogbloshie e-waste site was generated using Etiri GPS device. Findings showed that a total of 96.2% of all the study subjects had cuts and the dismantlers had a higher percentage amongst them all. Among the injuries, the prevalence of abrasion was 16.3% with a p-value of 0.038. This was statistically significant between the different activity groups. Scars were the most common skin condition. Prevalence of burns among the study subjects was 23.1% and with a p-value of 0.000, it could be said there was a significant association of sustaining burns with activity space. There was no significant difference in being hypertensive across all activity spaces. There were a total of 90.2% normotensive and 9.8% hypertensives among study subjects. 98.2% of respondents felt the need to have a first aid clinic at the site with 96.4% and 97.3% being willing to visit the clinic and pay for services respectively. Conclusion and Recommendations: Education of workers on the effective use of personal protective equipments, the use of modern equipments to disassemble e-waste materials and provision of alternatives to open burning of e-waste will help reduce the prevalence of injuries and skin conditions. First aid clinic at the site will be such a welcoming news for the workers.
Thesis (Mph) - University of Ghana, 2015
Keywords: E-Waste; Health Hazards; Environmental Pollution